Implementasi Tantangan dan Upaya dalam Mewujudkan Good Governance di Indonesia - Y, Angye Mareta; Frinaldi, Aldri; Roberia, Roberia (Al-DYAS, 2025)
This study aims to analyze the concepts, challenges, and strategies in realizing good governance in Indonesia through a literature review approach. Good governance is a basic principle of governance that includes transparency, accountability, public participation, law enforcement, and service effectiveness. The research method used is desk research, with data sourced from journal articles, books, research reports, and relevant policy documents. This research prioritizes literature published in the last 10 years to ensure the freshness and relevance of the data. The results show that although Indonesia has adopted the principles of good governance in various policies, its implementation still faces a number of challenges, such as weak law enforcement, low public participation, and lack of accountability in some government sectors. To address these challenges, this study recommends several strategies, including strengthening institutional capacity, information technology-based transparency, and increasing collaboration between the government, society, and the private sector. The conclusion of this study is that the implementation of good governance in Indonesia requires a holistic approach involving various parties and consistent efforts to improve the quality of governance. This research is expected to contribute to the development of public policies and better government practices in the future.